2016
DOI: 10.1016/j.ejvs.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Cardiac Troponin Assessment in Patients Undergoing Carotid Endarterectomy

Abstract: Troponin elevation after CEA occurred in 15% of patients. The incidence of adverse cardiovascular events was significantly higher in patients with troponin elevation, which was mainly attributable to silent non-ST segment elevation MIs that occurred in the early post-operative phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The authors suggested that perioperative myocardial injury cannot overcome the surgical stress, and inability to cope with the stress may have turned out as high mortality 29 . Furthermore, clinically silent troponin elevation from myocardial injury during postoperative period is known to increase the long-term mortality after major non-cardiac surgery 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that perioperative myocardial injury cannot overcome the surgical stress, and inability to cope with the stress may have turned out as high mortality 29 . Furthermore, clinically silent troponin elevation from myocardial injury during postoperative period is known to increase the long-term mortality after major non-cardiac surgery 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up included duplex ultrasound until 2 years of follow-up. The primary outcome was long-term MACE, defined as a composite outcome of non-fatal MI, AHF (onset of or de novo AHF), and all-cause mortality [6]. Secondary outcomes included all-cause mortality, stroke, MI, AHF, and major adverse limb events (MALE; defined as a composite outcome of major ischemic amputation, acute limb ischemia, and need for peripheral revascularization) [16].…”
Section: Methodsmentioning
confidence: 99%
“…The necessary sample for a survival test was calculated using WinPepi® v.11.65, aiming for statistical power (β) of 80% and a statistical significance of α <0.05. The described MACE rate in long-term post-CEA patients is approximately 6% [6]. The described event rates after 5 years of follow-up in stroke patients with normal and increased RDW-CV varies between 49 and 69% and 69 and 88%, respectively [17, 18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016) выявили, что у 15,1% пациентов, которым была выполнена КЭЭ под ОА, отмечалось повышение уровня тропонина I в первые трое суток после операции, а инфаркт миокарда в первые 30 дней развился у 3,6% [28]. Таким образом, клинически подтвержденный инфаркт миокарда наблюдался лишь у 23,5% пациентов с повышенным уровнем тропонина I после операции под ОА [28]. J. Pereira-Macedo и соавт.…”
Section: Discussionunclassified